The Case for Normalization: Linking Lexicographic Resources for Icelandic - Bjarnadóttir, Kristín (Nordiske Studier i Leksikografi, 2018)
The topic of this paper is the linking of two major lexicographic resources on Icelandic, the Dictionary of Old Norse Prose (ONP) in Copenhagen, and the Written Language Archive (WLA) at the Árni Magnússon Insti-tute for Icelandic Studies in Reykjavík. The resources would be linked by normalizing the headwords from the ONP to the standard used for Modern Icelandic spelling by the use of a spellchecker originally de-signed for use on Modern Icelandic. This is possible, as the major differ-ences in word forms between the two sources are mostly a matter of changes in spelling, whereas the morphology of Icelandic has been rela-tively unchanged through the centuries. Future work would consist of normalizing the citation collections themselves, thus creating a valuable resource linking variant word forms to their headwords or lemmas.